Деякі аспекти стратегічного планування розвитку житлово-комунального господарства - Попадюк, О.І. (Економіка промисловості, 2012)
Разработаны научно-практические рекомендации относительно формирования модели стратегического планирования развития отрасли жилищно-коммунального хозяйства.
Ключевые слова: жилищно-коммунальное хозяйство, стратегическое планирование, реформирование, государственное регулирование, тарифы ЖКГ. Розроблено науково-практичні рекомендації щодо формування моделі стратегічного планування розвитку галузі житлово-комунального господарства.
Ключові слова: житлово-комунальне господарство, стратегічне планування, реформування, державне регулювання, тарифи ЖКГ. The paper deals with working out of scientific and practical recommendations on building the model of strategic planning aimed at developing the housing and communal services.
To evaluate the effective work of the above sector the author offers the matrix “effective demand – quality levels of services”. Through the analysis of indifference curves it was revealed that the overall improvement may be extensive (as the welfare of the population) and intensive (through the active government management). The matrix “effective demand – quality levels of services” can be used to evaluate the effectiveness in three planes: “tariffs – quality + number of services” (describing the degree of availability of adequate housing and communal services), “payment for services – quality + number of services” (describing the financial condition of utilities), “adequacy of services – adequacy of payments” (level of market and government regulation of housing and communal services market).
To provide the effective reform and development of the sector, the combination of genetic and theological concepts of macroeconomic planning in two areas of public relations in the housing and communal services is needed – predominantly market regulation and active government policy: directive planning using a program-based approach to address the immediate problems of modernization of networks and equipment in this sector and indicative planning to improve the quality of housing and communal services.
Keywords: housing and communal services, strategic planning, reform, government regulation, tariffs for housing and communal services.